A Computer Interface for Radioisotope Data Processing - Knopp, Thomas J. (1972)
An interface for use with radioisotope disintegration counting has increased the efficiency and expanded the uses of radioisotopes in the study of dynamic phenomena. Counting periods as short as 0.1 sec can be used for several channels simultaneously providing rapid data acquisition and permitting storage on digital magnetic tape and/or real-time data analysis with a general purpose digital computer. Disintegration rates from several radioisotopes can be sampled simultaneously enabling corrections for count spill-over and background in real time. In the system described there are 6 channels (for up to 6 radioisotopes) but 12 may easily be incorporated.